Evidence Based Dyadic Therapies for 0- to 5-Year-Old Children With Emotional and Behavioral Difficulties - Shafi, Reem M. A.; Bieber, Ewa D.; Shekunov, Julia; Croarkin, Paul E.; Romanowicz, Magdalena (Frontiers in Psychiatry, 2019)
As many as 1 in 4 preschool-aged children are estimated to struggle with psychosocial stress and social-emotional issues; yet interventions are often postponed until older ages when change is actually more difficult. Reasons for this include limited interventions; paucity of FDA approved medications for young children, as well as the dearth of clinicians adequately trained in psychotherapeutic approaches for young children. This commentary outlines indications of the four most commonly used evidence-based dyadic psychotherapies for young children: Child-Parent Psychotherapy (CPP) and Trauma-Focused Cognitive Behavioral Therapy (TF-CBT), used primarily for young children with trauma, and Parent-Child Interaction Therapy (PCIT) and Child Parent Relationship Therapy (CPRT), used mostly for children with behavioral issues. Rooted in attachment theory and further supported by the premise that the quality of the child-caregiver dyad is paramount to psychological wellbeing, these therapies focus on strengthening this relationship. Literature indicates that insecure or disorganized early attachments adversely affect an individual’s lifelong trajectory. These therapies have demonstrated efficacy leading to positive behavioral changes and improved parent-child interactions. The major challenges of clinical practice focused on young children and their families include proper diagnosis and determining the best therapeutic strategy, especially for families who have not benefited from prior interventions. At this time, it is still unclear which therapy is best indicated for which type of patients and it mostly has been driven by convenience and provider preference or training. Further research is required to tailor treatments more successfully to the child’s needs.